Malaria exposure remodels the plasma proteome of Ghanaian children - Aisha M. Mohammed; Charles Ochieng’ Olwal; Andrea Fossati; Nancy K. Nyakoe; Jacqueline M. Fabius; Martin Gordon; Benjamin J. Polacco; Danielle L. Swaney; Gordon A. Awandare; Nevan J. Krogan; Mehdi Bouhaddou; Yaw Bediako (BMC Infectious Diseases)
Abstract Background Malaria, caused by Plasmodium falciparum, remains a major public health burden causing ~ 200 million deaths annually, especially among children. Although the lack of an effective vaccine has hindered malaria elimination, studies have reported on individuals acquiring natural immunity to malaria in the context of high malaria exposure. However, the immune correlates of protection in these people who acquire natural immunity against malaria are poorly understood. Methods Symptomatic children residing in high and low malaria transmission areas of Ghana were enrolled into the study and followed for 3 weeks from the day of malaria confirmation. The plasma proteome of these children was profiled using a mass spectrometry-based approach and putative protein-based biomarkers and predictors of immune tolerance to malaria were identified. Results We identified several differentially abundant proteins in children living in high malaria transmission areas relative to children in low transmission areas. Differentially abundant proteins were enriched in immune response processes, including complement cascade activities and elevated platelet activation. We found IGKV3D-20 protein to be strongly associated with high malaria exposure. Conclusions Our findings confirm earlier reports and identify putative signature proteins implicated in immune tolerance to malaria. Further large-scale and more mechanistic studies will be needed to reveal the key components of the identified pathways that could explain naturally acquired immunity to malaria and possibly be exploited to develop novel therapeutics against P. falciparum.